Mechanisms of initiation and progression of intestinal fibrosis in IBD. (January 2014) - Latella, Giovanni; Di Gregorio, Jacopo; Flati, Vincenzo; Rieder, Florian; Lawrance, Ian C.
Abstract Intestinal fibrosis is a common complication of the inflammatory bowel diseases (IBDs). It becomes clinically apparent in >30% of patients with Crohn's disease (CD) and in about 5% with ulcerative colitis (UC). Fibrosis is a consequence of local chronic inflammation and is characterized by excessive extracellular matrix (ECM) protein deposition. ECM is produced by activated myofibroblasts, which are modulated by both, profibrotic and antifibrotic factors. Fibrosis depends on the balance between the production and degradation of ECM proteins. This equilibrium can be impacted by a complex and dynamic interaction between profibrotic and antifibrotic mediators. Despite the major therapeutic advances in the treatment of active inflammation in IBD over the past two decades, the incidence of intestinal strictures in CD has not significantly changed as the current anti-inflammatory therapies neither prevent nor reverse the established fibrosis and strictures. This implies that control of intestinal inflammation does not necessarily affect the associated fibrotic process. The conventional view that intestinal fibrosis is an inevitable and irreversible process in patients with IBD is also gradually changing in light of an improved understanding of the cellular and molecular mechanisms that underline the pathogenesis of fibrosis. Comprehension of the mechanisms of intestinal fibrosis is thus vital and may pave the way for the developments of antifibrotic agents and new therapeutic approaches in IBD.